2017
DOI: 10.1371/journal.pone.0174721
|View full text |Cite
|
Sign up to set email alerts
|

Precocious obesity predisposes the development of more severe cisplatin-induced acute kidney injury in young adult mice

Abstract: Obesity and its consequences can damage the kidney over time. However, less is known about the impact of developing overweight/obesity during childhood on the kidney in adulthood and the renal impact of a superimposed acute kidney injury (AKI). This study evaluated the effect of obesity induced by a high-fat diet initiated soon after weaning on the adult life of mice and their response to superimposed nephrotoxic effects of cisplatin. C57BL/6 post-weaning mice (3 weeks old) were divided into a control group (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Recent chemotherapeutic agents are often associated with nephrotoxicity complications leading to minimizing the therapeutic doses and thus to limit the antitumor effect of those agents [47]. Moreover, in a recent study, Ribeiro et al [48] investigated the effect of obesity on the nephrotoxic effects of 20 mg/ kg of body weight of Cisplatin in mice. They found that Cisplatin causes acute renal injury especially to obese mice [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent chemotherapeutic agents are often associated with nephrotoxicity complications leading to minimizing the therapeutic doses and thus to limit the antitumor effect of those agents [47]. Moreover, in a recent study, Ribeiro et al [48] investigated the effect of obesity on the nephrotoxic effects of 20 mg/ kg of body weight of Cisplatin in mice. They found that Cisplatin causes acute renal injury especially to obese mice [48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent study, Ribeiro et al [48] investigated the effect of obesity on the nephrotoxic effects of 20 mg/ kg of body weight of Cisplatin in mice. They found that Cisplatin causes acute renal injury especially to obese mice [48]. The possible explanation for undetectable renal toxicity of GTN could be due to its anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a phosphodiesterase inhibitor and FDA approved compound, pentoxifylline, can systemically reduce inflammation and suppress synthesis of TNFα, preventing cisplatin nephrotoxicity in vivo [31]. Antioxidants such as Tempol [32], increased physical exercise [155], weight loss [156], and novel inhibitors such as Biochanin A [26] and Fasudil [47] have pleiotropic effects in addition to decreasing TNFα expression, with demonstrated in vivo renoprotective effects against cisplatin-induced AKI.…”
Section: Introductionmentioning
confidence: 99%
“…All data presented herein were obtained from refs. [44,54,55,70,72,74,75,78,88,95,96,98,[102][103][104][105][106][107][108][109][110][111]116,[119][120][121][124][125][126][127][128][129][130]132,[134][135][136][137][140][141][142][143][144][147][148][149][150][151][152][153][154]…”
Section: Resultsmentioning
confidence: 99%
“…All data presented herein were obtained from refs. [44,54,55,70,72,74,75,78,88,95,96,98,102–111,116,119–121,124–130,132,134–137,140–144,147–156,158,159,161,163–171,173–176...…”
Section: Diet Composition and Exposure Timementioning
confidence: 99%